Nivel de satisfacción del usuario con los cuidados de enfermería en el servicio de hospitalización de medicina del Hospital II - 2 Tarapoto. Abril - Julio del 2013 - Guevara Gil, Mary Yojani (2013)
The purpose of this study was to determine the level of user satisfaction with nursing care in the hospital medical service of Hospital II-2 Tarapoto. May-July 2013. During the development of pre-professional training was observed that some nurses medical service, have little initiative, interest and professional judgment to provide care to help solve the health problems of the hospitalized person. Is a simple descriptive study cross-sectional with prospective data collection, the sample consisted of 105 patients hospitalized in high process, in the service of medicine, was calculated by probability sampling, having with the average patient population expected in month selected inclusion criteria, with a confidence level of 95%. The technique of data collection was a survey with a structured survey instrument with 25 items with four response alternatives, measuring the level of satisfaction, using a rating scale of 0 - 3 points, whose indicators were: satisfied, dissatisfied and unfulfilled, according to results obtained showed that 100% (105) of inpatients discharged from the hospital medicine service Tarapoto II-2, 90.5% (95) were satisfied with nursing care, according to characteristics, 49.5% (52) ranged between ages of 38-47 years, there was a predominance of females with 59.0% (62) as the level of education 45.7% (48) had primary education, marital status, in the form of living together with 54 , 3% (57) and 41.0% (43) adults were in rural areas, according to the sub-dimensions of the quality of care is predominantly the most appropriate care, continuous with 81.0% (85) reported feeling satisfied, and 19.0% (20) said they were dissatisfied, and finally there is the risk free care with 77.1% (81) felt they were satisfied, and 22.9% (24) little satisfied, the level of user satisfaction with dimensions of care, the quality more variable is 95.2% (100) were satisfied and 4.8% (05) dissatisfied, and finally this warmth with 75.2% (79) reported be satisfied and 24.8% (26) Slightly satisfied. In conclusion, 90.5% of users are satisfied with nursing care are between the ages of 38-47, of females with level of education at the primary, with a civil state of living, housing location in area rural.